(untitled) - Moreno, Juan; Quintanilla, Hazel; 1982- ([Place of publication not identified], 2023)
"Duckie has an abundance of shoes: He has a pair of shoes for every activity he loves to do. Duckie's colorful shoes come in blue, red, green, and gray, which pair will he wear today? Parents will love this colorful bilingual English-Spanish board book as it introduces the concept of colors and the passing of time through the days of the week. An endearing duck will guide little ones through his bright closet of shoes--each one for a different day of the week and for a different activity."--Publisher.
Keywords: Novela juvenil; Spanish language materials; Novela juvenil; Zapatos; Bilingual; Patos; Fiction; Shoes; Ducks; Juvenile fiction; Shoes; Juvenile fiction; Ducks; Fiction; Board books